Hamstring Injury Rehabilitation and Prevention in the Female Athlete - Lucy O'Sullivan; Jamie Preszler; Miho Tanaka (International Journal of Sports Physical Therapy)
Hamstring injuries (HSIs) are common in female athletes and are associated with a lengthy recovery period and a high rate of reinjury. Currently, the majority of existing literature investigating HSI rehabilitation has been conducted using male participants. However, female athletes display intrinsic anatomical and biomechanical differences compared to males that influences the way this population experiences HSIs and HSI rehabilitation. HSI rehabilitation and injury prevention guidelines for female athletes must take these differences into account. Female athletes display anatomical differences such as increased anterior pelvic tilting, gluteus maximus weakness, an increased pelvic width-to-femoral length ratio, and an increased degree of femoral anteversion, all of which can predispose females to HSIs. Maneuvers designed to strengthen the gluteal musculature and transverse abdominis can overcome these risk factors. Females show increased joint laxity and a greater range of motion of hip flexion and internal rotation compared to males. Females have lower passive hamstring stiffness than males, therefore hamstring flexibility exercises may not be as necessary during rehabilitation for females as in the male athlete population. Female athletes may instead benefit from trunk stabilization exercises and agility training due to neuromuscular control deficits that arise from the maturation and growth of the female pelvis. Existing literature on hamstring injury prevention shows consistent use of the Nordic Hamstring Exercise and balance exercises may reduce the risk of sustaining an HSI in both males and females, though more studies are needed to ascertain the optimal regimen for injury prevention in the female athlete population specifically. The goal of this clinical commentary is to discuss sex-specific anatomic and biomechanical differences of the lumbar, pelvic, and hip regions with the aim of providing guidelines for rehabilitation and injury prevention of HSIs in female athletes.